Clinicopathological Study of Pleural Effusion In A Tertiary Care Hospital. (KYAMC Journal, 2022)
Background: Pleural effusion is an excess fluid that accumulates between two pleural layers. Pleural fluid analysis and cytology are the mainstays for diagnosing various pulmonary diseases. Levels of adenosine deaminase (ADA) are particularly useful in areas where the prevalence of tuberculosis is high.Objectives: To find the clinical profile and various etiology of pleural effusion in respect of age and sex and level of adenosine deaminase in the different causes of pleural effusion.Materials and Methods: This was an observational study carried out in the Department of Laboratory Medicine of a tertiary level teaching hospital, Khwaja Yunus Ali Medical College & Hospital (KYAMCH), Enayetpur, Sirajganj, Bangladesh. Biochemical analysis was done by Olympus AU-400 and cytology was done by Papanicolaou stain.Result: A total of 173 cases of diagnosed pleural effusion was taken in the present study. Tuberculosis was the primary etiology of the total 82 cases (47.39%), followed by malignancy accounting to 30 cases (17.34%). These two were followed by parapneumonic effusion (10.40%). ADA level is highest in TB (167U/L) in comparison with malignancy, transudative cause and other causes.Conclusion: Most common cause of pleural effusion in the tertiary hospital setting is tuberculosis, followed by malignant pleural effusion and ADA level is highest in TB than any other cause.KYAMC Journal Vol. 13, No. 02, July 2022: 98-101